The effect of nutrition education based on "MyPlate" Food Guidance on the anthropometric indices and blood profiles in patients with type 2 diabetes - Shima Shahmoradi; Mehrnoosh Zakerkish; Seyed Mahmood Latifi; Nafiseh Shokri; Mehdi Zarei; Majid Mohammadshahi (Tehran University of Medical Sciences, 2015)
Background & Aim: Adherence to the principles of appropriate nutrition and diet therapy is one of the most important aspects of diabetes management. The present study aimed to assess the effect of nutrition education based on "MyPlate" Food Guidance on the anthropometric indices and blood profiles in people with type 2 diabetes. Methods & Materials: In this randomized clinical trial study conducted in 2014, 44 people with type 2 diabetes were randomly allocated either into the control group or the intervention group. Anthropometric measurements, blood profiles, energy intake and physical activity data were collected before and three months after the 2 hours face-to-face "MyPlate" nutrition education session for the intervention group or the usual educational sessions for the control group. Paired t-test, independent sample t-test, ANCOVA, and nonparametric tests were utilized to analyze the data. Results: At the beginning of the study, the two groups were similar in terms of the anthropometric indices, glycosylated hemoglobin, blood sugar and physical activity. After intervention, except for physical activity which was higher in the nutrition education group based on "MyPlate" Food Guidance, the other above cases were lower than the control group (P<0.05), but no significant differences were seen in the changes of blood pressure (systolic and diastolic) and energy intake between two groups of education and control. Conclusion: Nutrition education based on "MyPlate" Food Guidance for three months decreases the anthropometric indices and blood profiles in people with type 2 diabetes.